Reflexive anaphor resolution in spoken language comprehension: structural constraints and beyond - Clackson, Kaili; Heyer, Vera (Frontiers in Psychology, 2014)
We report results from an eye-tracking during listening study examining English-speaking adults’ online processing of reflexive pronouns, and specifically whether the search for an antecedent is restricted to syntactically appropriate positions. Participants listened to a short story where the recipient of an object was introduced with a reflexive, and were asked to identify the object recipient as quickly as possible. This allowed for the recording of participants’ offline interpretation of the reflexive, response times, and eye movements on hearing the reflexive. Whilst our offline results show that the ultimate interpretation for reflexives was constrained by binding principles, the response time and eye-movement data revealed that during processing participants were temporarily distracted by a structurally inappropriate competitor antecedent when this was prominent in the discourse. These results indicate that in addition to binding principles, online referential decisions are also affected by discourse-level information.